Parental investment and body temperature explain encephalization in vertebrates - Zitan Song; Michael Griesser; Carel P. van Schaik (Proceedings of the National Academy of Sciences, 2025)
The systematic variation in relative brain size among vertebrate classes remains poorly understood. Here, based on the expensive brain hypothesis, we propose that two broad constraints explain much of the variation: 1) the ability to produce large offspring, and so provide them with the energy required for constructing larger brains, and 2) the ability to sustain continuously high body temperatures, because cooler and varying brain temperatures reduce brain performance and thus fitness. We therefore predicted that encephalization (major evolutionary increases in brain size) only happened where changes in physiology or natural history created these abilities. First, comparative analyses across all major vertebrate classes (n = 2600 species) revealed that protecting or provisioning eggs or embryos is associated with larger newborns. Subsequent analyses at the class level confirmed that newborn size and adult brain size underwent correlated evolution in birds, mammals, and cartilaginous fishes, but not in other fishes, amphibians, and reptiles. Second, we found a positive relationship between mean body temperature and brain size within each class (albeit sometimes insignificant). Third, a combined analysis across all vertebrates revealed a positive interaction between the effects of body temperature and newborn size. In conclusion, encephalization became most pronounced in vertebrate lineages that can both produce large offspring, reflecting internal fertilization with matrotrophy, and sustain high body temperature, partly linked to endothermy.